Plaque area at carotid and common femoral bifurcations and prevalence of clinical cardiovascular disease - Griffin, Maura B.; Nicolaides, Andrew N.; Tyllis, Theodosis H.; Georgiou, Niki; Martin, Richard Michael; Bond, Dawn; Panayiotou, Andrie G.; Tziakouri, Ch H.; Dore, Caroline J.; Fessas, Christian H. (My University, 2010)
Aim. Different ultrasonic arterial wall measurements have been used as predictors of future myocardial infarction or stroke. The aim of the present study was to determine the relationship of total plaque area (TPA) (the sum of the atherosclerotic plaque area measurements from both carotid and both common femoral arteries) with prevalence of cardiovascular disease in a population-based cross-sectional study and compare it with intima-media thickness (IMT). Methods. Seven hundred sixty-two individuals (47% male) over the age of 40 were screened for cardiovascular risk factors. Results. Evidence of clinical cardiovascular disease was present in 113 (14.8%). Both carotid and both common femoral bifurcations were scanned with ultrasound. After adjustment for conventional risk factors the association of IMT with prevalence of clinical cardiovascular disease was low (P=0.84, OR of upper IMT quintile 1.36; 95% CI 0.56 to 3.26) and of TPA high (P<0.001, OR of upper TPA quintile 8.38; 95% CI 2.57 to 27.32). TPA greater than 42 mm2 (cut-point derived from ROC curve analysis) identified 266 (34.9%) of the population that contained 87/113 (76.9%) of the clinical events (sensitivity: 77%; specificity: 73%; positive predictive value: 33%; negative predictive value: 94%; positive likelihood ratio of 2.79). In contrast, IMT greater than 0.07 mm had a sensitivity, specificity, positive and negative predictive value and positive likelihood ratio of 68%, 60%, 23%, 91% and 1.69 respectively. Conclusion. Total plaque area appears to be more strongly associated with the prevalence of cardiovascular disease than IMT. This finding warrants further prospective studies.
Keywords: Atherosclerosis; Cardiovascular diseases; Risk assessment; Ultrasonography